„Lechoń w Algierze”, czyli o pewnej (nieodegranej) roli dyplomatycznej - Dorosz, Beata (Archiwum Emigracji. Studia – Szkice – Dokumenty, 2012)
This paper is based on the unknown up to this point documents of the Ministry of Foreign Affairs of the Polish Government in Exile from 1943. It shows the authorities efforts to engage Jan Lechoń in the activity of Polish diplomacy by the French National Committee for Freedom chaired by gen. Ch. de Gaulle in Algeria. In this situation the poet’s experiences on the post of cultural attaché at the Polish Embassy in Paris before the war play a key role. The article reports the poet’s political views, his political and propagandistic activity in the circle of Polish émigré in the US as well as his personal feelings towards the government’s proposal and arguments which finally made him decide to give up this post.